Uso de herramientas tecnológicas y su incidencia en la pronunciación del Idioma inglés en estudiantes del segundo bachillerato de la unidad educativa padre Daniel Diez García en el cantón Simón Bolívar provincia del Guayas en el 2017 - Rosado Castro, María del Carmen (2017)
The present research project was carried out starting from a problem that was observed in the Educational in students Unidad Educativa Padre Daniel Diez Garcia of the 2 year of basic education where it was evidenced that the students have a low level of pronunciation of English, and that the teachers do not Are able to teach classes. It set targets that helped follow them to meet them and proposed to solve the problem. We inquired and conducted a survey of parents, teachers and students of the campus, to let us know their disagreement, after a detailed analysis and interpretation of data, we obtained the conclusions and recommendations to follow.The recommendations provided are of great importance because it is the joint idea of the group of respondents, among them we have the creation of a guide that shows the applications to be used to reinforce the classes already given, as well as bequeath to an agreement with the parents To be charge of their children while they are at home reinforcing the subject addressed. The proposal of this project is the implementation of technological tools and detailed which of them are easier and less expensive that could be used in students, are applications that teach you in a fun and especially easy to understand and speak the language English.